Leaf color as an indicator of the accumulation pattern of pharmaco-nutritional compounds in Lithocarpus litseifolius spring foliage - Zhao, Pengxia; Yang, Zhiling; Tan, Zifeng; Yang, Yixun; Tian, Zhaoxia; Yang, Xu (Frontiers in Plant Science, 2025)
Lithocarpus litseifolius leaves are rich in pharmaco-nutritional compounds such as phlorizin and trilobatin, and their spring foliage exhibits vibrant colors. However, the relationship between leaf color and the levels of these compounds remains unexplored. This study investigated the growth patterns of naturally variegated Lithocarpus litseifolius and measured the pharmaco-nutritional component content using UV-Vis and HPLC, along with the correlation between these components and leaf color. The results showed that spring foliage followed an S-shaped growth curve, while total flavonoid content of the pharmaco-nutritional components exhibited a multi-peak accumulation pattern, initially increasing before declining. Trilobatin levels peaked on April 3 and April 8, whereas phlorizin reached its highest level on May 31. The flavonoid composition of different-colored leaves varied consistently during leaf development, with reddish-brown (RBL) and orange (OL) leaves containing the highest levels. Correlation analysis revealed a significant positive relationship between redness (a*) and flavonoid content—higher anthocyanin levels corresponded to greater flavonoid accumulation. Thus, the optimal period for tea preparation is early April, while late May, at full leaf maturity, is ideal for pharmaceutical harvest. The reddish-brown (RBL) and orange (OL) leaves, having the highest flavonoid content, are best suited for breeding. Therefore, the strong correlation between leaf color and flavonoid composition suggests that color can serve as a morphological indicator for assessing flavonoid accumulation.